Isolation and characterization of mesenchymal stem cells from umbilical cord of giant panda. (August 2021) - Liu, Yuliang; Li, Feiping; Cai, Zhigang; Wang, Donghui; Hou, Rong; Zhang, Hao; Zhang, Ming; Yie, Shangmian; Wu, Kongju; Zeng, Changjun; An, Junhui
Graphical abstract: Highlights: The first report of UC-MSCs isolation, cultivation and identification in giant panda. UC-MSCs from giant panda were positive for MSC markers and pluripotency genes. bFGF and EGF promoted giant panda UC-MSCs proliferation. Adipocyte, osteoblast and chondrocyte were successfully induced from giant panda UC-MSCs. Abstract: Umbilical cord-derived mesenchymal stem cells (UC-MSCs) constitute a class of cells with significant self-renewal and multilineage differentiation properties and have great potential for therapeutic applications and the genetic conservation of endangered animals. In this study, we successfully isolated and cultured UC-MSCs from the blood vessels of giant panda umbilical cord (UC). The cells were arranged in a vortex or cluster pattern and exhibited a normal karyotype, showing the morphological characteristics of fibroblasts. In addition, we found that basic fibroblast growth factor (bFGF) and epidermal growth factor (EGF) promoted cell proliferation, whereas stem cell factor (SCF) did not promote cell proliferation. Cultured UC-MSCs were negative for CD34 (hematopoietic stem cell marker) and CD31 (endothelial cell marker), but positive for MSC markers (CD44, CD49f, CD105, and CD73) and stem cell markers (KLF4, SOX2, and THY1). Similar to other MSCs, giant panda UC-MSCs have multiple differentiation ability and can differentiate into adipocytes, osteoblasts and chondrocytes. Giant panda UC-MSCs are new resources for basic research as cell models following their differentiation into different cell types and for future clinical treatments of giant panda diseases.